1978
DOI: 10.1017/s0022112078002700
|View full text |Cite
|
Sign up to set email alerts
|

The motion of a large gas bubble rising through liquid flowing in a tube

Abstract: The theory presented here describes the motion of a large gas bubble rising through upward-flowing liquid in a tube. The basis of the theory is that the liquid motion round the bubble is inviscid, with an initial distribution of vorticity which depends on the velocity profile in the liquid above the bubble. Approximate solutions are given for both laminar and turbulent velocity profiles and have the form \begin{equation} U_s = U_c+(gD)^{\frac{1}{2}}\phi(U_c/(gD)^{\frac{1}{2}}), \end{equation}Us being the bubbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
104
1
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(112 citation statements)
references
References 7 publications
(16 reference statements)
6
104
1
1
Order By: Relevance
“…The flow is supposed to be inviscid and rotational, the upstream vorticity distribution being determined by a given velocity profile. Collins et al [2] have obtained expressions for the bubble velocity, which agree well with the experimental results and the results of Bendiksen taken into account the influence of the surface tension. In the horizontal case, the theoretical analysis of Benjamin [4] showed that, the drift velocity is equal to V ∞ = 0.542 √ gD in a horizontal tube and V ∞ = 0.5 √ 2ga in a channel (D is the tube diameter and 2a is the height of the channel).…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…The flow is supposed to be inviscid and rotational, the upstream vorticity distribution being determined by a given velocity profile. Collins et al [2] have obtained expressions for the bubble velocity, which agree well with the experimental results and the results of Bendiksen taken into account the influence of the surface tension. In the horizontal case, the theoretical analysis of Benjamin [4] showed that, the drift velocity is equal to V ∞ = 0.542 √ gD in a horizontal tube and V ∞ = 0.5 √ 2ga in a channel (D is the tube diameter and 2a is the height of the channel).…”
Section: Introductionsupporting
confidence: 73%
“…It is appropriate particularly for the flows in which exists an interface where viscous shearing can be neglected due to the fact that the vorticity diffusion closes to the interface remains negligible. It is the case for axis-symmetric bubbles in vertical pipes which was treated successfully by Collins et al [2] and by Bendiksen [3].…”
Section: Formulation Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicklin et al (1962), Grace and Clift (1979), and Fabre and Liné (1992), among others, obtained these values experimentally. Collins et al (1978) arrived at very close values. Polonsky et al (1999) carried out simultaneous measurements of the velocity profiles ahead of the Taylor bubble using particle image velocimetry (PIV) and of the bubble propagation velocity in undeveloped laminar and turbulent pipe flow.…”
Section: Introductionmentioning
confidence: 84%
“…Another group of authors [10][11][12][13] have stated that for a fully developed gas-liquid two-phase upward slug flow, the translational propagating velocity is independent of the length of the Taylor bubble. The intricacies of obtaining fully developed gas-liquid flow relies on bubbles expansion caused by the pressure changes along the tubing as it rises from the bottom, leading to increase in bubble volume thereby affecting its motion.…”
mentioning
confidence: 99%